(untitled) (REMUNOM, 2023)
The judgment of Theme 1.102 of the Federal Court of Justice on the Lifetime Review was perhaps the most awaited decision of the year 2022. The present work will discuss the historical scenario since the Real Plan, going by the advent of Law 9.876/99, which changed the wording of art. 29, I and II, of Law 8.213/91, by Constitutional Amendment n. 103/2019 (EC 103/19), which dealt with the Social Security Reform, until the publication of the judgment of the decision in 2023. Therefore, the entire analysis of the factual framework that the review is inserted in aims to verify whether there was a right violated during two decades of oppressed rights, given the non-accounting of social contributions prior to July 1994 and which could have significantly increased the values received by policyholders. Thus, during the elaboration of the research, the deductive and historical methodology was adopted, analyzing the doctrine and legislation, as well as observing an entire social context. Therefore, with the research it was possible to confirm the possibility of including the contributions made prior to 1994 in the face of the favorable judgment to the insured.